Difficult Removal of a Stuck Chemoport Catheter of a Paediatric Patient in Post-Coronavirus Disease (COVID-19) Era – Management Strategies and Literature Review - Chuah Jun Sen; Yoong Chee Cheng (African Journal of Paediatric Surgery, 2024)
A chemoport is widely used in paediatric oncology population. Removal is a relatively easy procedure, but difficulty can be encountered in case the catheter is densely adherent to the vascular wall. It is a rare complication and is associated with long indwelling duration and acute lymphoblastic leukaemia (ALL). Forceful traction can lead to vascular injury and high morbidity. Herein, we report a 7-year-old girl with precursor B ALL who had delayed chemoport removal due to the coronavirus disease (COVID-19) pandemic. The removal process was difficult, as the catheter was adherent to the right innominate vein. Out of panic, the surgeon pulled it out forcefully. Fortunately, the catheter and its fragment were successfully retrieved completely and the child was discharged the next day. The management strategy varies and ranges from minimally invasive to open surgery. Leaving a stuck chemoport catheter in situ can be a bailout method or part of conservative management.